"Making Cents" of the Eastern Australian Gas Market. Issue 1 (25th October 2017) - Quentin Grafton, R.; Shi, Xunpeng (Roc); Cronshaw, Ian
Abstract : The paper reviews the causes of high domestic gas prices and possible future gas shortfalls in the Eastern Australian gas market. It explains the economics of gas pricing, the effects of long‐term gas contracts on domestic supplies and prices, and examines the incentives faced by gas exporters. Policies to respond to concerns over gas supply and high domestic gas prices are explored and alternatives presented.